Increasing Students’s Higher Order Thinking Skills Through Developing Scientific-Based Learning Scenarios - Ririn Setyowati; Novia Rahma Rista Utami (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
The results of the PISA survey in 2015 and 2018 have decreased, indicating that the Higher Order Thinking Skills of students are not optimal so that more effective learning scenarios are needed. The purpose of this study is (1) to describe the characteristics of scientific-based learning scenarios, (2) the development of scientific-based learning scenarios, and (3) to determine the effectiveness of scientific-based learning scenarios to improve students' HOTS. This research and development use a modified method Sukmadinata and Thiagajaran, et al. which consists of define, design, development and disseminate phases. The research subjects were fourth-grade students of Elementary Schools in Ngawi Regency. Data collection techniques used the HOTS test and teacher and student response questionnaires. The HOTS data analysis technique used Independent Sample T-Test based on the pretest and posttest gain scores in the experimental and control groups. The results of the gain score analysis show a significance level of 0.019 less than = 0.05 so that H0 is rejected, which means that there are differences in the HOTS students in the experimental and control groups. This shows that the use of scientific-based learning scenarios can increase the HOTS fourth-grade students at Elementary Schools in Ngawi Regency